(untitled) (Swiss Medical Weekly, 2010)
Background/aims: Skin tumours, in particular squamous-cell carcinomas (SCC), are the most common malignant conditions developing in transplant recipients. The aim of this study is to investigate the frequency and type of skin cancer in patients receiving immunosuppressive therapy after organ transplantation. Methods: Multivariate logistic regression analysis was performed on data of 243 renal transplant patients who attended the dermatology outpatient clinic for the first time after transplantation in the period January 2002–October 2005. Results: We found an increased risk of actinic keratosis (AK) and SCC in renal transplant recipients with a basal cell carcinoma (BCC) / SCC ratio of 1:7. Older patients had AK more frequently (odds ratio [OR] 1.11, 95% confidence interval [CI] 1.06–1.15; p <0.0001) and SCC (OR 1.14, CI 1.07–1.22; p <0.0001) than younger patients. Men had AK (OR 0.19, CI 0.08–0.45; p = 0.0002) and SCC (OR 0.25, CI 0.07–0.89; p = 0.0332) more frequently than women. The duration of immunosuppressive therapy correlated significantly with the numbers of AKs (OR 1.15, CI 1.08–1.24; p <0.0001) and SCCs (OR 1.16, CI 1.05–1.28; p = 0.0025), and patients with fair skin had more AKs (OR 0.31, CI 0.14–1.24; p <0.0001) and SCCs (OR 0.11, CI 0.02–0.52; p = 0.0054) than darker skinned patients. We could not identify any specific immunosuppressive drug as a distinct risk factor for AK or non-melanoma skin cancer (NMSC). Conclusion: Skin cancers are increased in the renal transplant population. Main risk factors for skin cancers are fair skin type and long duration of immunosuppressive therapy. A follow-up programme is necessary for early detection of skin cancer and precancerous conditions. Preventive strategies should include specialist dermatological monitoring and self-examination.